ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KELANCARAN PENGEMBALIAN KREDIT PADA KOPERASI WANITA DI KABUPATEN BANTUL - Nurul Atiqoh Mahardika; Zulfatun Ruscitasari; Galuh Ratna Mutia (Profit : Jurnal Inovasi Ekonomi dan Bisnis, 2023)
Cooperatives are people's economic institutions that aim to promote and prosper members and the community to create a just and prosperous society. ABC Women's Cooperative collects member funds through savings and loan activities. At the ABC Women's Cooperative there are problems that arise, namely bad loans by members. This study aims to find out what factors influence the smooth return of credit for the ABC Women's Cooperative and how the strategy for resolving bad loans at the ABC Women's Cooperative. This research uses a descriptive qualitative method. The data was obtained directly from the ABC Women's Cooperative through observation data collection techniques and interviews. The results of this study indicate that the factors that influence the smooth return of credit at the ABC Women's Cooperative are gender, marital status, moral behavior, household size, loan payments, business age, profit margin, business risk, interest rate, grace period, skills and training, and strategies in overcoming bad loans at the ABC Women's Cooperative are focused on being caught after the pandemic by prioritizing the interests of members and helping the needs of cooperative members by going through a strategy of rescheduling, reconditioning, and restructuring. This is evidenced that the latest data and the informants' answers are valid according to the current situation in the field.